2014
DOI: 10.1002/aic.14540
|View full text |Cite
|
Sign up to set email alerts
|

Partial oxidation of methane in hollow‐fiber membrane reactors based on alkaline‐earth metal‐free CO2‐tolerant oxide

Abstract: The U-shaped alkaline-earth metal-free CO 2 -stable oxide hollow-fiber membranes based on (Pr 0.9 La 0.1 ) 2 (Ni 0.74 Cu 0.21 Ga 0.05 ) O 41d (PLNCG) are prepared by a phase-inversion spinning process and applied successfully in the partial oxidation of methane (POM) to syngas. The effects of temperature, CH 4 concentration and flow rate of the feed air on CH 4 conversion, CO selectivity, H 2 /CO ratio, and oxygen permeation flux through the PLNCG hollow-fiber membrane are investigated in detail. The oxygen pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Shao et al [139] reached a stable and relatively high oxygen flux of 8.6 × 10 −6 mol cm −2 s −1 using a BSCF planar membrane. Contrary to many other studies [219] that reported that the BSCF material interacts with the CO 2 , the authors could keep a long-term (500 h) experiment without any noticeable change in the POM performance.…”
Section: Partial Oxidation Of Methane (Pom)mentioning
confidence: 70%
“…Shao et al [139] reached a stable and relatively high oxygen flux of 8.6 × 10 −6 mol cm −2 s −1 using a BSCF planar membrane. Contrary to many other studies [219] that reported that the BSCF material interacts with the CO 2 , the authors could keep a long-term (500 h) experiment without any noticeable change in the POM performance.…”
Section: Partial Oxidation Of Methane (Pom)mentioning
confidence: 70%
“…During the past two decades, mixed oxygen ion‐ and electronic‐conducting membranes have received considerable attention as novel ways to separate oxygen from air at substantially reduced energy consumption . The permeation of oxygen through a mixed conducting membrane is based on the simultaneous diffusion of oxygen ions and electrons through the membrane bulk using the drive force of an oxygen potential difference across the two surfaces of the membrane .…”
Section: Perovskite Materials For Energy‐related Applicationsmentioning
confidence: 99%
“…Mixed ionic‐electronic conducting (MIEC) oxides are a kind of multi‐functional materials. It can be applied as high active cathodes for solid oxide fuel cells (SOFCs), as membranes for oxygen separation with infinite selectivity, as catalytic membrane reactors for selective oxidation or reduction reactions, integrated with oxy‐fuel process for CO 2 capture . Among these applications, MIEC materials as oxygen separation membranes producing high purity oxygen at elevated temperature is promising to be commercialized in the near future due to its low costs and high efficiency compared with pressure swing adsorption and cryogenic distillation technologies .…”
Section: Introductionmentioning
confidence: 99%